Occupancy of avian foraging guilds in soybean fields and borders in Entre Ríos, Argentina: responses to vegetation structure and prey resources - Goijman, Andrea Paula; Conroy, Michael J.; Varni, Vanina Delia; Thompson, Jeffrey; Zaccagnini, Maria Elena (BMC, 2020)
Reconciling agriculture and biodiversity conservation is a challenge given the growing demand for agricultural products. In recent decades, Argentina has witnessed agricultural expansion and intensification affecting biodiversity and associated ecosystem services. Within agroecosystems, the level of habitat quality is critical for birds, and may depend on vegetation structure, availability of invertebrate prey, and the use of pesticides. Although the relationship between vegetation structure and avian occurrence has been widely studied, to our knowledge, there are no studies that also incorporate prey availability throughout the cycle of soybean crops in Argentina. We estimated and predicted the effects of land cover and temporal variation on the occurrence of avian foraging guilds in Entre Ríos, Argentina, in order to guide management related to potential ecosystem services provided by birds. We also estimated temporal effects of vegetation structure and insecticides on the main arthropod orders consumed by birds to evaluate prey availability. Methods: We conducted bird and arthropod surveys for 2 years along transects located in 20 randomly selected soybean fields (N = 60) and their adjacent borders (N = 78) throughout the crop growing season, in four seasons. We estimated avian occupancy, accounting for imperfect detection, and arthropod counts fitting generalized linear mixed models. Results: The number of native trees in field borders positively influenced the occurrence of most bird species, mainly insectivores. Granivore foliage gleaners, also were positively affected by grass height. Salliers and aerial foragers were weakly affected by distance to forest and native trees. In general, the availability of invertebrates to birds was highest during the third season. Arthropod counts in borders were greater during the last three crop stages than during the pre-sowing period. Conclusions: We found that with 10 to 15 native tree species in borders, coupled with a complex vegetation structure with shrubs and grasses, we could conserve a wide spectrum of insectivorous birds, and may contribute to the invertebrate pest control service. Vegetated field borders function as a refuge for arthropods, especially agriculturally beneficial taxa such as Hymenopterans. Finally, several groups of birds use the interior of the fields and could help control pests.